2022
DOI: 10.1021/acsomega.2c00093
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-Doped Activated Coconut Shell Carbon-Anchored Highly Dispersed Pt for the Chemoselective Hydrogenation of Nitrobenzene to p-Aminophenol

Abstract: Highly dispersed Pt nanoparticles (∼2.5 nm) on phosphorus-doped activated coconut shell carbon (Pt/P-ACC) were synthesized by a two-step impregnation route. Pt/P-ACC showed a high activity, chemoselectivity, and reusability toward the hydrogenation of nitrobenzene to p -aminophenol, with hydrogen as the reducing agent in sulfuric acid. The effects of P species on the catalyst structure, surface properties, and catalytic performance were investigated. It was found that the Pt/P-ACC cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These results confirm the strong electronic interactions between PtRuP and the NiO@TiO x support. A comparison of the conversion and selectivity of dissimilar catalysts (Figure 3F) showed that us‐PtRuPNiNiO@TiO x has the highest catalytic efficiency among the reported Pt‐based catalysts 22–27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm the strong electronic interactions between PtRuP and the NiO@TiO x support. A comparison of the conversion and selectivity of dissimilar catalysts (Figure 3F) showed that us‐PtRuPNiNiO@TiO x has the highest catalytic efficiency among the reported Pt‐based catalysts 22–27 …”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the conversion and selectivity of dissimilar catalysts (Figure 3F) showed that us-PtRuPNiNiO@TiO x has the highest catalytic efficiency among the reported Pt-based catalysts. [22][23][24][25][26][27]…”
Section: Catalytic Performance Of Us-ptm-nio@tiomentioning
confidence: 99%
“…The intermediate PHA can be converted into PAP by acid-catalyzed Bamberger rearrangement, and thus, the influence of acid concentration on the selectivity of PAP was examined. As shown in Figure d, the acid concentration ranged from 0 to 1.13 M under the standard reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…para -Aminophenol (PAP) is a key raw material in chemical industry, which is widely used in the fields of photosensitive materials, medicine, dyes, pesticides, and rubber. Traditionally, the industrial production process of PAP involves starting from raw materials such as phenol, p -nitrophenol, p -nitrochlorobenzene, and nitrobenzene (NB). Among them, the iron powder reduction method using p -nitrophenol as raw material is the earliest route for producing PAP. However, this method inevitably produces a large amount of wastewater and iron sludge with high cost and serious pollution and is rarely used now.…”
Section: Introductionmentioning
confidence: 99%
“…50 Moreover, being stabilized by positively charged L4, these small sized Pd NPs offers a large and suitable surface for long range (CH 3 ) 2 N + -----À O-N + (-Ph-R)=O interaction. 51 Sodium borohydride as a reductant release H 2 on the surface of Pd NPs without affecting it and also provide the necessary basic pH for the reaction. 52 The released H 2 and nitro-aromatics altogether get facilitated to react over the surface of Pd-L4 NPs through the reaction, that is, S C H E M E 3 Pd-L4 NPs catalyzed reduction of nitro-aromatic compounds in the presence of other reducible groups.…”
Section: Catalytic Application Of Pd-lnpsmentioning
confidence: 99%